Peran GCG dalam Memoderasi Struktur Modal dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Ade Onny Siagian; Adler Haymans Manurung; Tri Widyastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the role of GCG in moderating Capital Structure as proxied by DAR and DER, Company Growth on Company Value. This research uses quantitative methods with 35 companies for the 2019-2022 period as samples in this research. Sampling used a purposive sampling method. The analysis method uses Eviews 12. The results of this research variable DAR have a probability value of less than 0.05; the DER variable has a probability value of more than 0.05; the growth variable has a probability value of more than 0.05. The f test results have a probability value of less than 0.05. The partial conclusion is that DAR has a negative and significant influence on company value, while DER and growth have no effect on company value..